(untitled) (Applied Biological Research, 2023)
The fishing cat (Prionailurus viverrinus) is a medium-sized wild cat with a sporadic distribution in mangroves, wetlands, rivers, and swamps in parts of South and Southeast Asia (Nowell and Jackson, 1996). The fishing cat is in the red list of IUCN as vulnerable (IUCN, 2016). The fishing cat is the state animal of West Bengal (India). The leopard cat (Prionailurus bengalensis) is a small wild cat native to the South and East Asia (Ross et al., 2015). Since 2002, it has been assessed as least concern on the IUCN red list as it is widely distributed but threatened by habitat loss and hunting in parts of its range (Ross et al., 2015). The small Indian civet (Viverricula indica) is a civet found in South and Southeast Asia. It is in the least concern list of IUCN because of its wide geographical distribution (Choudhury et al., 2015). Scapula is an important bone responsible for the movement of forelimb. The research related to the biometrical analysis of scapula of fishing cat, leopard cat and small Indian civet are lacking, so the present investigation was conducted.